Sorting Out Animal Policy: Ideas, Problems, and Solutions - Jerry Mitchell (International Review of Public Policy)
Animals are the focus of public policy around the world. Nonetheless, animal policy has not been established as a separate domain. This article describes the elements of animal policy to clarify its scope for public discourse and to give it a distinct research status. Three perspectives on animal policy are identified—anthropocentrism, animal welfare, and natural rights. Each of these ideas shapes the responses to the policy issues of animal cruelty, species disruptions, and the use of animals for public service. By ordering various problems and solutions within animal policy, an illustration is provided of how policy coherence can inform public discourse and governance.